2015
DOI: 10.1039/c5cp02689j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hierarchical ZnO/CdS heterostructured nanocomposites for enhanced hydrogen evolution from solar water splitting

Abstract: ZnO/CdS heterostructured nanocomposites were fabricated with enhanced light harvesting capability and photostability using sequential sonochemical and hydrothermal methods from ZnO rods and particles. Interestingly, in the composite made up of CdS sensitized ZnO rods, both ZnO and CdS exist in the hexagonal wurtzite form with different morphologies. On the other hand, in the composite made up of CdS sensitized ZnO particles, ZnO exists in the hexagonal wurtzite form, whereas CdS in the cubic form but with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…For example, Mukhopadhyay et al reported hierarchical ZnO/CdS nanocomposites with enhanced photocatalytic water‐splitting performance . ZnO nanorods and mesoporous ZnO nanoflowers were firstly prepared through sequential sonochemical and hydrothermal methods.…”
Section: Application Of Direct Z‐scheme Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mukhopadhyay et al reported hierarchical ZnO/CdS nanocomposites with enhanced photocatalytic water‐splitting performance . ZnO nanorods and mesoporous ZnO nanoflowers were firstly prepared through sequential sonochemical and hydrothermal methods.…”
Section: Application Of Direct Z‐scheme Photocatalystsmentioning
confidence: 99%
“…For example, Mukhopadhyay et al reported hierarchical ZnO/CdS nanocomposites with enhanced photocatalytic water splitting performance. [59] ZnO nanorods and mesoporous ZnO nanoflowers were firstly prepared through sequential sono chemical and hydrothermal methods. Then, the prepared ZnO nanorods and mesoporous ZnO nanoflowers were coupled with CdS NPs to form ZC1 and ZC2 direct Zscheme photo catalysts, respectively (Figure 18a-d).…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…Enhanced H 2 production through the decoration of ZnO nanoparticles has already been observed for ZnS and CdS nanocomposites as well. 46,47…”
Section: A Cathode Based On Cu Foam Coated With Zn Nanoflakes For Elmentioning
confidence: 99%
“…Previous literatures have reported the syntheses of ZnO and CdS heterostructures to form respective hybrid systems, which are used to improve the efficiency of hydrogen production and stability. [24][25][26] For instance, X. W. Wang , which is 13 and 138 times higher than that of single ZnO. 3 S. Mukhopadhyay et al prepared disk ZnO by an ultrasonic chemical method, then deposited CdS nanoparticles on the disk surface using a hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen production efficiency of the composite was 22 times higher than that of single ZnO in visible light. 26 Although these results of the above works are promising, the synthesis of ZnO/CdS heterostructures requires high temperatures and complex preparation methods, which are energy-consuming procedures.…”
Section: Introductionmentioning
confidence: 99%